Analisis Tingkat Produktivitas Karyawansebelum Dan Sesudah Penerapan Konsep Leanmanufacture Pada PT Sanggar Sarana Baja - Rezki Amalia Syahrir; Longginus Gelatan; Tuti Fitriani; Ignasius Narew; Ahmad Tomu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine differences in the analysis of employee productivity levels before and after the implementation of the lean manufacturing concept at PT Sanggar Sarana Baja in Mimika Regency. The research method used in this study is a comparative research method. The data used are qualitative and quantitative data collected using observation techniques, questionnaires and documentation. To measure the difference in the level of employee productivity before and after the application of the lean manufacturing concept at PT Sanggar Sarana Baja, Mimika Regency, the Wilcoxon Match Pair Test analysis was used. The results of this study indicate that there are differences in the level of employee productivity before and after the application of the lean manufacturing concept seen from the timeliness aspect which is very influential in supporting the achievement of company targets. Keywords : Productivity, Quantity, Quality, Timeliness, Lean Manufacture